FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN DEPRESI PADA PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUP DR. M. DJAMIL PADANG - Zahra Zafira; Yuliarni Syafrita; Amel Yanis (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2026)
Patients with Chronic Kidney Disease (CKD) require hemodialysis due to a decrease kidney function. This hemodialysis procedure can have psychological impacts, one of which is depression. Suspected contributing factors include age, gender, education, duration of hemodialysis, comorbidities, and socioeconomic status. This observational analytical study utilized a cross-sectional design involving 47 CKD patients in the Hemodialysis Unit of Dr. M. Djamil Padang Hospital. The sample was selected using consecutive sampling. Depression screening was assessed with Patient Health Questionnaire (PHQ-9). Results indicate 61.7% of CKD patients experience depression, notably prevalent in individuals aged over 51 years (62%), females (55.17%), with lower education (51.1%), undergoing hemodialysis for over 6 months (75.85%), with hypertension comorbidity (86.2%), without diabetes mellitus comorbidity (96.55%), and with low socioeconomic status (75.86%). Chi-square analysis identified age (p=0.018) is a significant factor, while gender (p=0.432), education level (p=0.693), duration of hemodialysis (p=1.000), hypertension comorbidity (p=0.692), diabetes mellitus comorbidity (p=1.000), and socioeconomic status (p=0.455) are not significantly related. This study concluded that age is a significant factor related to the occurrence of depression in CKD patients, while gender, education level, duration of hemodialysis, comorbidities, and socioeconomic status do not have a significant relationship with the occurrence of depression in CKD patients.